2007
DOI: 10.1590/s0104-42302007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Uso de tabaco e perfil lipídico-lipoprotéico plasmático em adolescentes

Abstract: RESUMO OBJETIVO.Analisar o impacto quanto ao uso de tabaco no perfil lipídico-lipoprotéico plasmático em amostra representativa de adolescentes. MÉTODOS. A amostra foi constituída por 452 sujeitos (246 moças e 206 rapazes) com idades entre 15 e 18 anos. Os participantes completaram questionário estruturado auto-administrado com relação ao uso de tabaco. As concentrações de lipídeos-lipoproteínas plasmáticas foram estabelecidas mediante procedimentos laboratoriais. Os procedimentos da análise de covariância, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
2
0
3
Order By: Relevance
“…had a mean TG difference of 29.1 points lower than those who smoked more than 5 cigarettes a day (n = 26; p = 0.02) [41]. These conclusions have been replicated in several other studies, both in pediatric and adolescent populations [42] [43].…”
Section: Active Smokingsupporting
confidence: 60%
“…had a mean TG difference of 29.1 points lower than those who smoked more than 5 cigarettes a day (n = 26; p = 0.02) [41]. These conclusions have been replicated in several other studies, both in pediatric and adolescent populations [42] [43].…”
Section: Active Smokingsupporting
confidence: 60%
“…Our results were in synchrony with the studies conducted by Guedes et al . [16] and Sliwinska-Mosson et al . [17] Lipoproteins, in order of molecular size, largest to smallest, are chylomicrons, (VLDL), intermediate-density lipoprotein, LDL, and HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was observed that the adolescents who smoked used medications mostly for occasional problems. Recent studies have shown a positive association between smoking and occasional medicine use,8 indicating that tobacco causes harm to health both chronically7 and acutely 21…”
Section: Discussionmentioning
confidence: 99%